Exploring the Role of Islamic Hospitals in Healthcare: A Bibliometric Analysis and Future Research Directions - Putranto, Ega Dwi; Aini, Qurratul (Indonesian Journal of Global Health Research, 2024)
This study aims to find out the development of research with the theme of Islamic Hospitals in the range of 2015 to 2024. This research is important because the research explores the development of studies on Islamic Hospitals and offers future research themes. This study uses a qualitative research method with a bibliometric approach to analyze the research trends of Islamic Hospitals. The research data is sourced from peer-reviewed publications of leading journals and conferences in the fields of health, information technology, and management, with an emphasis on reputable international journals indexed by Scopus. The collected data is then thoroughly analyzed and visualized with the VOSviewer program. The method used makes it easy to identify key bibliometric variables and provides a perspective on the patterns and characteristics of Islamic hospital studies over a specified period of time. The findings of this study show that bibliometric analysis provides useful information about Islamic hospital academics. Publications have increased significantly, peaking in 2019. Medical research is very productive in Islamic hospitals. Bali Medical Journal is well-known in this profession. Indonesia leads this field in research. Hasina, S.N. and Setianto, B. are the most prolific researchers. The scientific work at Universitas Airlangga is very impressive. For the 42 authors, having two or more papers is significant. The author uses "human" more than any other term. So Human, Adult, Male and female, these topics have become the focus of the study of Islamic Hospitals. However, there are still some topics such as religion, middle aged and nurse that are open for further research. The ongoing research trend reflects the increasing efficiency in strengthening the practices of Islamic hospitals, which it is hoped that this will contribute to progress in th.